Development and validation of a physical activity educational module for overweight and obese adolescents: CERGAS programme - Lau, Xiao Chuan; Wong, Yaw Loong; Wong, Jyh Eiin; Koh, Denise Choon Lian; Sedek, Razalee; Jamil, Ahmad Taufik; Ng, Alvin Lai Oon; Abu Saad, Hazizi; Abd Talib, Ruzita; Poh, Bee Koon (MDPI, 2019)
Educational modules can be effective in educating and motivating adolescents to participate in physical activity (PA). This paper describes the development and validation of a PA educational module for use in an obesity intervention programme, CEria Respek Gigih Aktif Sihat (CERGAS). The present study was conducted in three phases: Phase I was composed of needs assessments with four focus group discussions to elicit adolescents’ opinions regarding module content and design, Phase II was the development of the PA module, while Phase III was content and face validation. A content validity index (CVI) was used to assess content validity quantitatively, with a CVI of more than 0.79 being considered appropriate. The needs assessments indicated that content of interest to adolescents included: the benefits of exercise; exercise techniques; ways to increase PA and how to stay motivated. Attractive graphic design was determined as a way to draw the adolescents’ attention. The module covered five topics: “Let’s Be Active”; “Exercise and Fitness”; “Staying Safe during Exercise and Physical Activity”; “Planning for Success” and “How to Overcome Sedentariness and Get Moving”. The module was found to have good content validity (mean CVI = 0.85). Expert members made suggestions to improve the module. These suggestions were then accepted, and the module was modified accordingly. We concluded that the module has good content validity and can be used to improve PA knowledge amongst CERGAS participants.